Nanophytoplankton and microphytoplankton in the western tropical Pacific Ocean: its community structure, cell size and carbon biomass - Yan, Wenzhuo; Chen, Zhuo; Zhang, Linlin; Wang, Feng; Zhang, Guicheng; Sun, Jun (Frontiers in Marine Science, 2023)
Phytoplankton, as a crucial component of the marine ecosystem, plays a fundamental role in global biogeochemical cycles. This study investigated the composition and distribution of phytoplankton in the western Tropical Pacific Ocean using the Utermöhl method and carbon volume conversion. We identified four primary groups of phytoplankton: dinoflagellates (181 species), diatoms (73 species), cyanobacteria (4 species), and chrysophyceae (2 species). The clustering analysis classified phytoplankton into four groups based on their composition, which were found to be closely related to ocean currents. Diatoms were highly abundant in areas influenced by current-seamount interaction. In contrast, areas with little influence from ocean currents were dominated by Trichodesmium. The majority of phytoplankton had an equivalent spherical diameter (ESD) of 2-12 μm, with a few exceeding 25 μm. Although nanophytoplankton (ESD = 2-20 µm) dominated cell abundance, microphytoplankton (ESD = 20-200 µm) contributed significantly to carbon biomass (792.295 mg m-3). This study yielded valuable insights into the distribution and composition of phytoplankton in the western tropical Pacific Ocean, shedding light on the relationship between species distribution and ocean currents. In addition, it provided fundamental information regarding cell size and carbon biomass within the region.